The story of the Philippines the Eldorado of the Orient - Halstead, Murat 1829-1908. ([Chicago] Our Possessions Pub., 1898)
"The complete book in PDF format"--CD-ROM label.
This is a reproduction of the original edition.
Distributed by FELTA Multi-Media.
Keywords: Philippines -- Description and travel